2015
DOI: 10.1371/journal.pone.0123498
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Barrier in Irritable Bowel Syndrome: Subtype-Specific Effects of the Systemic Compartment in an In Vitro Model

Abstract: BackgroundIrritable bowel syndrome (IBS) is a disorder with multifactorial pathophysiology. Intestinal barrier may be altered, especially in diarrhea-predominant IBS (IBS-D). Several mediators may contribute to increased intestinal permeability in IBS.AimWe aimed to assess effects of tryptase and LPS on in vitro permeability using a 3-dimensional cell model after basolateral cell exposure. Furthermore, we assessed the extent to which these mediators in IBS plasma play a role in intestinal barrier function.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…An increased serum LPS concentration has been reported in patients with IBS-D compared with HS (24). Endotoxins, which are a component of the outer membrane of Gram-negative bacteria, stimulate various inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…An increased serum LPS concentration has been reported in patients with IBS-D compared with HS (24). Endotoxins, which are a component of the outer membrane of Gram-negative bacteria, stimulate various inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…30) TRYP increases the permeability of colon tissue in diarrhea-predominant IBS patients. 31) A study conducted by Ludidi et al revealed that TRYP can increase the permeation flux of 4-kDa fluorescein isothiocyanate-labelled dextran (FD4) in Caco-2 cells, indicating an effect of enhancing paracellular permeability and intestinal barrier dysfunction. 32) In our study, we induced Caco-2 cell monolayers with TRYP, and this treatment reduced the TEER and increased the PFP.…”
Section: Discussionmentioning
confidence: 99%
“…This "competition" is called colonization resistance and is an important guarantee of the normal functioning of the gastrointestinal system. Certain important molecules, which may include short-chain fatty acids (SCFA) and bacteriocins, are implicated in the course of colonization resistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…SCFA lowers the pH around the intestinal epithelial cells that has a protective effect on them. Besides, SCFA provide antibacterial protection against pathogenic bacteria by attracting neutrophils and cytokines, with immune tolerance to commensal flora remaining [4]. It is believed that different SCFA can have various effects, in particular, butyrate is more present in the intestine, propionate -in the enterohepatic circulation, acetate -in the systemic circulation [4,6].…”
Section: Introductionmentioning
confidence: 99%